The Quality of European Societies A Compilation of Composite Indicators - Bericat, Eduardo; Jiménez-Rodrigo, María Luisa (Social Indicators Research Series,, 2019)
This volume presents a compilation of composite indicators created in order to measure important aspects of the quality of European societies. It examines three main questions: do Europeans live in good societies and enjoy good lives; are European societies becoming better as time passes, or is their quality slowly deteriorating; is the quality of life of Europe's citizens improving over time or is it gradually and irrecoverably getting worse. The volume uses a precise and rigorous system of information to answer these questions and to assess the current situation and monitor the quality of European societies. It describes and discusses fourteen key domains, and per chapter, presents five rankings of EU countries based on composite indicators, which are used as one of the best instruments social science has to synthesize a large amount of information, and they are especially well suited to measure multidimensional social phenomena. The new System of Indices on the Quality of European Societies (SIQES) presented in this volume offers a very broad and rich empirical overview of more than 70 social composite indicators and their nearly 300 dimensions. One of the key findings coming out from the SIQES is that, according to the societal quality of European countries, there exist five different "Europes" inside Europe.